Improving Students’ SpeakingSkillsl Using Throw Ball Games at Islamic Boarding School - Nailul Authar; Mujad Didien Afandi (Community Development Journal, 2023)
The aims of the community service is to improve the students’ speaking skills through communicative games. And the subject for this research is coming from 10 students from Tahfidzul Quran Boarding School who has been selected. The communicative games implemented was a Throw the Ball game. This activity will be conducted in four stages: the pre-activity, the general stage, which includes the activity's launch, the core stage, and the stage of evaluation. The pre-activity is the first stage. The data was gotten from interviews and observation. The findings showed good improvement to students’ speaking skills. Most students enjoy the game while laughing, some students are a little confused when suddenly asked questions and cause their answers to go round and round, students are forced to get out of the situation and they succeed. Moreover, students hold highly positive attitudes about the role of games in improving their speaking skills.